Effect of early enteral feeding on recovery profile in mild acute pancreatitis - Chandran, Kailash; Mammen, Sam Christy (International Surgery Journal, 2020)
Background: Acute pancreatitis is a pestilent disease with severity ranging from mild and self-limiting to a rapidly progressive illness leading to multi organ failure. Mild acute pancreatitis is inflammation of the pancreas with minimal remote organ involvement. Since the disturbance in the homeostasis is minimal, the treatment aims at supporting the native reparative processes of the body. One of the main supportive mechanisms is adequate nutritional supplementation. Gut barrier damage in the early phase of acute pancreatitis accounts for the bacterial translocation, initiation of sepsis, infected pancreatic necrosis and SIRS. Aim of the study was to determine the feasibility, advantages and disadvantages of early enteral nutrition in mild acute pancreatitis. Methods: 40 patients taken consecutively from units which start enteral feeds before 48 hours (study group) were compared against 40 patients taken consecutively from units where patients will be kept fasting for 48 hours (control group) to determine whether early enteral feeding is better in determining the recovery in terms of duration of hospital stay, reduction in abdominal symptoms and use of analgesics. Results: There was significant reduction in the duration of hospital stay (p=0.011), intensity and duration of abdominal pain, need for analgesics, and risk of oral food intolerance in the study group. Conclusions: Patients with mild acute pancreatitis can safely be started on early enteral feeds. It reduces gastro intestinal adverse effects, abdominal pain and need for analgesics and improves oral food tolerance causing shorter hospital stay.